Cycling biomechanics optimization - the (r) evolution of bicycle fitting - Swart, J.; Holliday, W. (Current Sports Medicine Reports, 2019)
Optimal bicycle configuration has been the topic of numerous studies. A majority of these have investigated the optimal saddle height and have used either static kinematics or two-dimensional kinematic measurements. Other joints, such as the hip, shoulder, and elbow joint, have not been investigated to any meaningful extent. There is, therefore, a paucity of data describing the optimal position of the upper body and pelvis in cycling. More recently, it has been recommended that bike fitting be conducted in a dynamic functional manner, as kinematics can be influenced by cycling workload. Full-body three-dimensional kinematics and saddle pressure are newer modalities available to the clinician. This review of the literature investigates the current research pertaining to the configuration of all components of the bicycle, from static methods to dynamic methods, and related to optimal performance and injury prevention. Setting the saddle height using the Holmes static method is optimal for injury prevention and performance. Guidelines for optimal bicycle configuration should take into account the training intensity when assessing kinematics as compensatory lower-limb kinematics occur during higher-power outputs. Optimal KFA using dynamic measurements should range from 33° to 43° at low intensity to 30° to 40° at high intensity when measured at the bottom dead center crank position. Saddle pressure mapping should ideally be performed at an intensity similar to what cyclists will encounter during the majority of their training and racing. Reference values and recommendations for dynamic assessments are still required for all other joints. Furthermore, intrinsic factors, such as training load and flexibility, which may affect bicycle configuration and performance, should be investigated to assess how these may influence the optimal bicycle configuration.